Role Of News Portals In Political Communication Through Instagram : A Study - Nirman, Vishwadeep (The journal of contemporary issues in business and government, 2021)
A news portal is an access point to news through internet service. This is generally thought of as a Internet connection to a news source but the definition of a “Portal” would include a newspaper, magazine or any other access to news which is also a part of media convergence today. Many news portals in India have evolved in the last decade and because of internet service these portals have active users. In the study the content has been analysed which is disseminated through given news portals.The response of the users and its impact has been analysed through content analysis. As political parties mostly utilize the online platforms to flow the persuasive message to the mass. In many scenario like political campaigning and image building news worthy information is disseminated through such portals.News portals such as The Wire, The Print and The News Laundry has a wide range and active users in India. Mostly youngsters are using these portals through instagram nowadays. [1]Their daily interviews, news analysis has been seen as the effective content to which users respond and give feedback in real time itself.The study has been conducted around these three news portals and the content has been analysed to study the appeals, likes, comments in political communication.